Properties of Logarithmic function











\(\;\bullet\;\; \log_{e}(ab)= \log_{e} a +\log_{e} b \;\;\;\;\;\;\;\;\;\;\;\;\;\;\; \left \{a,b>0 \right \}\)

\(\;\bullet\;\; \log_{e}\left ( \displaystyle \frac{a}{b}\right )= \log_{e} a -\log_{e} b \;\;\;\;\;\;\;\;\;\;\;\;\; \left \{a,b>0 \right \}\)

\(\;\bullet\;\; \log_{e} a^{n}= n\log_{e} a \;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\; \left \{a>0 , n \in \mathbb{R} \right \}\)

\(\;\bullet\;\; \log_{a} a= 1 \;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\; \left \{a>0 ,a \neq 1 \right \}\)

\(\;\bullet\;\; \log_{a^n} b=\displaystyle \frac{1}{n} \log_{a}b \;\;\;\;\;\; \left \{a,b>0 ,a \neq 1, n \in \mathbb{R} \right \}\)

\(\;\bullet\;\; \log_{a} b=\displaystyle \frac{1}{\log_{b}a} \;\;\;\;\;\; \;\;\;\;\;\;\;\;\;\;\;\; \left \{a,b>0 ,a,b \neq 1 \right \}\)

\(\;\bullet\;\; \log_{a} b=\displaystyle \frac{\log_{n}b}{\log_{n}a} \;\;\;\;\; \left \{a,b>0 ,a,b \neq 1 ,n>0\right \}\)

\(\;\bullet\;\; a^{ \log_{a} n}=n \;\;\;\; \;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\; \left \{a,n>0 ,a \neq 1 \right \}\)

\(\;\bullet\;\; \displaystyle a^{ \log_{m} n}=n^{\log_{m}a} \;\;\;\;\;\;\;\;\;\;\;\;\;\;\; \left \{a,m,n>0 ,m \neq 1 \right \}\)

\(\;\bullet\;\; \displaystyle \log_{n} a=b \Rightarrow a=n^b \;\; \left \{a, n > 0\;; n \neq 1, b \in \mathbb{R} \right \}\)

\(\;\bullet\;\; \displaystyle \log_{n} x > \log_{n} y \Rightarrow \left\{\begin{matrix} \;\;\;\;\;\;\;\;\;\;\;\; x > y\;\;if\;\;n > 1\\ x < y\;\;if\;\; 0 < n < 1 \end{matrix}\right. \)

\(\;\bullet\;\; \log_{n} a > b \displaystyle \Rightarrow \;\;\;\;\;\;\;\;\;\;\;\; \left\{\begin{matrix} a > n^b\;\;if\;\; n > 1\\ a < n^b \;\;if\;\; 0 < n < 1 \end{matrix}\right.\)

\(\bullet \log_{n} a < b \displaystyle \Rightarrow \;\;\;\;\;\;\;\;\;\;\;\; \left\{\begin{matrix} a < n^b \;\;if\;\; n > 1\\ a > n^b\;\;if\;\; 0 < n < 1 \end{matrix}\right.\)

Post a Comment

0 Comments